Clinical relevance of postoperative proteinuria for prediction of early renal outcomes after kidney transplantation - Junseok Jun; Kyungho Park; Hyun Suk Lee; Kyo Won Lee; Jung Eun Lee; Jae Berm Park; Kyunga Kim; Wooseong Huh; Yoon-Goo Kim; Dae Joong Kim; Hye Ryoun Jang (The Korean Society of Nephrology, 2022)
Background Proteinuria is associated with poor allograft and patient survival in kidney transplant recipients. However, the clinical relevance of spot urine protein-to-creatinine ratio (PCR) or albumin-to-creatinine ratio (ACR) as predictors of renal outcomes during the early postoperative period following kidney transplantation (KT) has not been determined. Methods This single-center retrospective cohort study included 353 kidney transplant recipients who underwent KT between 2014 and 2017 and were followed up for more than 3 years. Among them, 186 and 167 recipients underwent living donor KT and deceased donor KT, respectively. The PCR and ACR were measured during the immediate postoperative period (within 7 days postoperatively), before discharge (2-3 weeks postoperatively), and 3-6 months postoperatively. Results The median age of the patients was 51 years (interquartile range, 43-59 years), and 62.9% were male. An immediate postoperative PCR of ≥1 mg/mg was associated with old age, diabetes mellitus, high systolic blood pressure, delayed graft function, and donor factors (deceased donor KT, old age, and high serum creatinine concentrations). The PCR and ACR 3 to 6 months posttransplant were inversely associated with the estimated glomerular filtration rate at 1 year posttransplant. Deceased donor KT recipients with immediate postoperative PCR of ≥3 mg/mg showed a greater incidence of delayed graft function and lower estimated glomerular filtration rate before discharge than those with immediate postoperative PCR of <3 mg/mg. Conclusion Early postoperative proteinuria is a useful biomarker to predict early renal outcomes after KT.